Inclisiran - hope in the fight against dyslipidemia - Krawiec, Paulina; Madej, Karolina; Wolanin, Izabela; Zielonka, Bartłomiej; Kowalczyk, Ilona; Stachyra, Bartłomiej; Wolanin, Marta; Stawikowski, Cezary; Dengler, Barbara; Osińska, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction:Lipid disorders are one of the most common modifiable risk factors for cardiovascular disease. Until now, the mainstay of dyslipidemia treatment was the use of widely available statins. These drugs, despite significantly lowering cholesterol and bringing its concentration to desired values were associated with a number of side effects. In addition, the need for daily use of statins is inconvenient for patients and leads to their irregular use and, consequently, failure to achieve the desired effect. The new drug, inclisiran, which is a PCSK9 inhibitor, represents the future in the treatment of lipid disorders. Studies conducted to date have explored the drug's mechanism of action, frequency of administration to achieve the desired effect, and side effects. The results of these studies have confirmed the significant efficacy of inclisiran,which may become a major form of treatment for dyslipidemia in the future. Purpose of the work: This article reviews the state of knowledge based on available studies on inclisiran. The aim of the review is to present the most important information about this drug related to the mechanism of action, effects on the body or assessment of efficacy. Materials and methods: The authors, based on databases such as PubMed, Scopus and Google Scholar, created a paper summarizing a review of currently available publications, concerning a new drug in the treatment of dyslipidemia- inclisiran. The authors searched for available information , using terms under the heading "key words" contained in other scientific papers. Summary Inclisiran is a novel drug that represents the future in the treatment of dyslipidemia. Due to the lack of systemic effect, it has insignificant side effects, and the need for such rare administration will allow to obtain the desired lipid concentrations even in patients who do not cooperate.